The first records on the socioenvironmental degradation in the amazon: the amazon depression after the first cycle of rubber (1920-1940) in the data of the brazilian general censuses - Cantagalo, Michel (Revista Hipótese, 2020)
The first records of the socioenvironmental degradation of the Amazonian biome were analyzed in this paper through the available data from Brazilian General Censuses. Utilizing the data, several indexes are presented to facilitate the comprehension of the Amazônia conditions after the first rubber cycle. The evidence brought from the analysis, point that the Amazonian problem is secular, contradicting the mainstream literature that defends that the region’s problem only gets relevant in the 1970s.
Keywords: Amazônia; Economic History; Regional Economics